Synthesis and refractive index dispersion properties of the N,N?,N-trinaphthylmethyl melamine-DDQ complex thin film - Arslan, M.; Atak, F. B.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2007)
The synthesis and optical properties of the N,N',N-trinaphthylmethyl melamine-DDQ complex thin film were investigated by the optical characterization. The optical constants such as refractive index and absorption coefficient were determined and the refractive index dispersion was analyzed by the single-effective oscillator model. The single oscillator energy E-o and the dispersion energy E-d were calculated. The effect of temperature on refractive index dispersion and optical band gap is also discussed. Consequently, the annealing temperatures have an important effect on the absorption edge and refractive index of the thin film. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: optical constant; single oscillator; annealing temperature